Performing ethnicity: Beyond constructivism to social creativity - Clammer, John (Social alternatives, 2017)
It is widely accepted that the notions of 'race' and 'ethnicity' are socially constructed: they do not refer to any objective underlying genetic or visible phenotypical characteristics, but, like the notion of gender, are rather social extrapolations from those essentially biological factors. This is evidently true up to a point, but it has its serious dangers. It can lead for example to an overly sociological concept of ethnicity, one in which, in the words of the anthropologist Manning Nash.